2014
DOI: 10.3390/ijms151017751
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression of a Novel Fungal Immunomodulatory Protein with Human Tumor Cell Antiproliferative Activity from Nectria haematococca

Abstract: To our best knowledge, all of the fungal immunomodulatory proteins (FIPs) have been successfully extracted and identified in Basidomycetes, with only the exception of FIP from ascomycete Nectria haematococca (FIP-nha) discovered through homology alignment most recently. In this work, a gene encoding FIP-nha was synthesized and recombinantly expressed in an Escherichia coli expression system. SDS-PAGE and MALDI-MS analyses of recombinant FIP-nha (rFIP-nha) indicated that the gene was successfully expressed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Characterization of the FIP-like sequence from the ascomycete Nectria haematococca was reported (Bastiaan-Net et al, 2013), while the manuscript was being prepared (Li et al, 2014). The other FIP-like sequence was found in the genome database of the basidiomycete P. placenta Mad-698-R (http://www.jgi.doe.gov/Postia).…”
Section: Heterologous Expression Purification and Identification Of mentioning
confidence: 98%
“…Characterization of the FIP-like sequence from the ascomycete Nectria haematococca was reported (Bastiaan-Net et al, 2013), while the manuscript was being prepared (Li et al, 2014). The other FIP-like sequence was found in the genome database of the basidiomycete P. placenta Mad-698-R (http://www.jgi.doe.gov/Postia).…”
Section: Heterologous Expression Purification and Identification Of mentioning
confidence: 98%
“…placenta ) that were expressed in E . coli significantly inhibited the growth of several types of cancer cells and induced apoptosis, and the anti-tumour effects were cell-specific [18, 19]. These results indicated that, despite the sequence conservation between FIPs from different sources, their anti-tumour activity varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers have shifted away from the extraction or homologous cloning methods for identifying new FIPs and instead search for sequence similarity in the burgeoning genome databases. Two previously unknown FIP genes were quickly identified by genome mining and were largely produced using recombinant expression [1719]. These two FIPs were very different from previously discovered FIPs: FIP-nha was the first FIP that was identified from the ascomycete Nectria haematococca , and FIP-ppl from Postia placenta was the only basidiomycete FIP to be identified outside the order of Macrofungi.…”
Section: Introductionmentioning
confidence: 99%
“…From that date, six other FIPs in species of the genus Ganoderma have been reported: FIP-gts of G. tsugae (15), FIPgsi of G. sinensis (16), FIP -gja of G. japonicum (Genbank: AAX9824), FIP-gmi G. Microsporum (17), FIP-gas of G. atrum (GenBank: KM077027.1) and FIP-gap G. applanatum (Genbank: AEP68179). Other eleven fungal immunomodulatory proteins have been described at molecular or sequence level in other Basidiomycetes: FIP-fve of Flammulina velutipes (18), FIP-vvo of straw mushroom (19), FIP-Apl of Auricularia polytricha (20), FIP-aca of Antrodia camphorate (21), FIP-PCIP Pleurotus citrinopileatus (22), FIP-PCP of Poria cocos (23), FIP-tvc of Trametes versicolor (24,25), FIP-ppl Postia placenta (26), FIPcru Chroogomphis rutilus (27), FIP-Lrh of Lignosus rhinocerotis (Tiger milk mushroom) (28), FIP-tfu of Tremella fuciformis (GenBank: EF152774) and FIPnha Nectria haemotococca edge Ascomycetes (29).…”
Section: Discoverymentioning
confidence: 99%
“…For several FIPs there is an experimental description of the basic DNA encoding sequence of the gene, and the primary, secondary and tertiary conformation of the protein (33,43,71). There are also insights about their effects on the immune system of vertebrate (29,69), however it is not known in depth the molecular mechanism that triggers the immunomodulatory response (26,72).…”
Section: Bioactivity In Model Systemsmentioning
confidence: 99%